Analisis in silico peptida berasaskan epitop daripada protein-protein imunogen Burkholderia pseudomallei - Yi, Wan Seow; Zhi, Yun Tan; Chieng, Sylvia (Penerbit Universiti Kebangsaan Malaysia, 2022)
Melioidosis is an infectious disease caused by the gram-negative bacterium Burkholderia pseudomallei. This disease is associated with high human mortality rate, especially in tropical and subtropical regions. Rapid diagnosis is crucial in ensuring proper management and treatment of the disease with effective antibiotics. Currently, melioidosis diagnosis, bacterial culture is time consuming, difficult, and not sensitive, while IHA is hindered by high antibody background in healthy population and ELISA lacks standardization and is hindered by antigen inconsistency. To improve the current diagnosis method for melioidosis, this research aims to identify, screen, and develop epitope-spanning peptides to be used as standardized B. pseudomallei antigen in serodiagnosis of melioidosis. Peptides are favoured as they are more stable, and they offer effective and rapid antibody detection. Using in silico analysis, a pool of 154 B. pseudomallei proteins previously reported as immunogenic were screened and ranked based on their antigenicity, subcellular localization, stability, adhesive properties, and ability to interact with class I and class II major histocompatibility complex (MHC). The selected candidate from the analysis, BPSS0908 and BPSL2152 were then taken for further analysis to identify linear B-cell epitopes using several sequence-based B-cell epitope prediction tools. Consensus sequences that are confidently predicted by more than two prediction tools and are longer than 15 amino acids were then selected as linear B-cell epitopes. Through ELISA analysis, low sensitivity was demonstrated by the epitope-spanning peptides as compared to B. pseudomallei crude lysate. However, high specificity of 100% was observed for all tested peptides. The low sensitivity demonstrated by the peptides in ELISA could be due to lack of 3-dimensional structure which is needed for a stable antigen-antibody binding.